The Brazilian Atlantic Forest genus Bocagea (Annonaceae) revisited, with two new species - Mello-Silva, Renato; de Carvalho Lopes, Jenifer (Phytotaxa, 2020)
Bocagea, a distinctive genus of tribe Bocageeae (Annonaceae), is revisited here. It is endemic to the Brazilian Atlantic Forest and has been for almost 200 years represented by only two species, B. longepedunculata and B. viridis. Recent collections from Espírito Santo and São Paulo States produced two new species, described here. The species of Bocagea are rare plants, all of them classified at least as endangered.